Supporting data for "Diel variability of methane emissions from lakes" - Sieczko, Anna Katarzyna (Linköping University, 2020)
In this study, we performed lake CH4 flux measurements resolving diel variability in four lakes with different physicochemical characteristics, which are situated along a climate gradient from the northern temperate to northern boreal zone. We used a combination of manual and automated flux chambers, which generated 4,580 individual
flux estimates, covering in total 524 full chamber measurement days in the lakes.

The dataset was originally published in DiVA and moved to SND in 2024.
Supporting data for "Diel variability of methane emissions from lakes"
Keywords: emissions; utsläpp; lakes; sjöar; greenhouse gases; växthusgaser; methane; metan; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap